Integrating specification and programs for system modeling and verification - SUN, Jun (Institutional Knowledge at Singapore Management University, 2009)
High level specification languages like CSP use mathematical objects as abstractions to represent systems and processes. System behaviors are described as process expressions combined with compositional operators, which are associated with elegant algebraic laws for system analysis. Nonetheless, modeling systems with non-trivial data and functional aspects using CSP remains difficult. In this work, we propose a modeling language named CSP# (short for communicating sequential programs) which integrates high-level modeling operators with low-level procedural codes, for the purpose of efficient mechanical system verification. We demonstrate that data operations can be modeled as terminating sequential programs, which can be composed using high-level compositional operators. CSP# is supported by the PAT model checker and has been applied to a number of systems.